PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. TSI - Vicka Arvianti; Puji Isyanto (JOURNAL SAINS STUDENT RESEARCH, 2024)
Teraoka Seisakusho Indonesia is a company engaged in adhesive tape, then in the sale of the products offered have many types of adhesive tape that will be exported to various countries but in reality this company has several obstacles, namely development and training are still not good. The purpose of this study is to find out whether there is a significant influence related to the influence of job training on employee productivity at PT. TSI The method used is a descriptive method with a qualitative approach with the help of a tool, namely SPSS.